2007
DOI: 10.1007/s00421-007-0508-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of maximal oxygen uptake from the ratings of perceived exertion and heart rate during a perceptually-regulated sub-maximal exercise test in active and sedentary participants

Abstract: This study assessed whether the accuracy of predicting maximal oxygen uptake (VO2max) from sub-maximal heart rate (HR) and ratings of perceived exertion (RPE) values was moderated by gender and habitual activity. In total, 27 men and 18 women completed two GXTs to determine VO2max and three perceptually-regulated GXTs, incremented by RPE 9, 11, 13, 15 and 17. The RPE and HR were individually regressed against VO2max (approximately 0.96) to enable predictions of VO2max. The VO2max was predicted from three RPE r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
0
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 37 publications
11
79
0
16
Order By: Relevance
“…It is possible that the participants' familiarity with regular exercise in this study may affect their ability to perceptually regulate specific intensities according to a given, prescribed RPE. In this regard, Faulkner et al, 10 observed that able-bodied, physically active individuals showed less variability in reproducing a given exercise intensity at prescribed RPEs across several trials.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is possible that the participants' familiarity with regular exercise in this study may affect their ability to perceptually regulate specific intensities according to a given, prescribed RPE. In this regard, Faulkner et al, 10 observed that able-bodied, physically active individuals showed less variability in reproducing a given exercise intensity at prescribed RPEs across several trials.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10 This might be attributed to the lower mechanical efficiency during arm cranking compared with leg cycling as a result of recruiting additional muscles for stabilizing the torso and from static work of some muscle groups, which do not contribute to the external work rate. 19,20 In conclusion, this study has shown a very strong linear relationship between the RPE and .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations